Penggunaan Media Digital Interactive Flat Panel (IFP) Terhadap Peningkatan Motivasi Belajar Matematika Siswa - Afrida Jaya Asmara; Lora Widjayanti; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
This study aims to find and analyze in depth. This study uses a qualitative research paradigm with a case study approach. Research respondents consist of school principals, class teachers, and sixth grade students. Data collection methods use participatory observation, in-depth interviews, and documentation. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. The results of the study show that (1) The use of Interactive Flat Panel (IFP) has a significant positive impact on students' motivation to learn Mathematics; (2) Interactive IFP features such as learning videos, animations, simulations, interactive quizzes, and digital whiteboards can create a fun learning atmosphere, improve understanding of abstract concepts, and encourage active student participation; (3) Students show increased enthusiasm, confidence, and involvement in learning. The conclusion of the study is that the use of Interactive Flat Panel (IFP) digital media can increase students' motivation to learn Mathematics.